Screening Indonesian Medical Plants Phytochemistry Using Molecular Docking as Hepcidin Antagonis in Iron Deficiency Anemia - Adiparadana, Dien; Suselo, Yuliana Heri; ., Balgis (Nexus Kedokteran Translasional, 2015)
Background: Iron deficiency anemia is found in clinical practice and community. There is mutasion in a genetic within iron deficency anemia which regulate iron homeostatis.Mutation in the TMPRSS6 resulting in iron refractory iron deficiency anemia Â The TMPRSS6 genetic encoding matriptase-2 enzymes which regulate hepcidin. The hepcidin is a principal regulator of iron homeostatis. Indonesia have more than 2.000 medical plants which have many roles and function. Some plants have phytochemisty that potentially in hepcidin antagonis. The phytochemistry is screen using molecular docking method Methods: The research design was a biocomputasion. It had been done at Medical Faculty of Sebelas Maret University on August-Oktober, 2014. The data was collected by using purposive sampling method. All data is docked using Autodock Vina in PyRx software. Docked sample is compared with binding energy of furstulhiamine drug. The data was compared its binding energy and their zone interaction with fursulthamine Results: The result were 10 samples has higher its binding energy than fursulthiamine. The binding energy of fursulthiamine was -6,7 kcal/mol. The highest binding energy was -8,5 kcal/mol and the lowest was -8 kcal/mol. All 10 sample interacted with cys 326. The cys 326 was the residue which can inhibit hepcidin interaction with ferroportin Conclusions: The Molecular Docking can be used to intial screening many phytochemisty. The result was 10 phytochemistry Indonesian medical plants which may inhibit hepcidin interaction. Further research is needed to prove the effect of phytochemistry. Keywords: Hepcidin, molecular docking, phytochemistryÂ